Molecular interaction of cryptophycin 52 with Caspase 8 for the management of lung cancer during coronavirus outbreak : A computational study: Cryptophycin 52 with Caspase 8 for the lung cancer - Leena Hussein Bajrai; Sayed Sartaj Sohrab; Mohammad Khalid; Mohammad A. Kamal; Esam Ibraheem Azhar (Cellular and Molecular Biology, 2022)
It has been seen that, during COVID-19 outbreak lung cancer (LC) patients are noted as a high-risk population which make a more challenging to treatment of the LC patients. The active form of caspase-8 is involved in lung carcinogenesis in both humans and mice. In this study, the virtual screening was performed among 200 compounds retrieved from several resources for the searching of potent lead against Caspase 8 (Casp8). Cryptophycin 52 was found to have a strong inhibiting efficacy based on the free energy of binding with the active site of Casp8. The lowest binding energy was found to be -8.05 kcal/mole and was further analyzed for molecular dynamic simulation. Casp8 enzyme was determined to interact with cryptophycin 52 through twelve amino acid residues, specifically ARG260, SER316, GLY318, ASP319, THR337, VAL354, PHE355, PHE356, ILE357, GLN358, ALA359 and CYS360 along with six hydrogen bond particular, ILE357:N-UNK1: O7, UNK1: O14-PHE355:O, UNK1: C25-PHE355:O, UNK1: C35-THR337:O, UNK1: H65-HE355:O and UNK1: C25-PHE356. In addition, MD simulations for 50ns were performed for optimization, flexibility estimation and assessment of Casp8-cryptophycin 52 complex stability. This complex was seen as reasonably stable according to the RMSD, RMSF, and radius of gyration graph. Results obtained indicate cryptophycin 52 may be a lead compound with significant anti-cancer ability against Casp8. Further experimental work, however, is expected to support the compound’s anti-cancer viewpoint.